Secular government, religious people - Lupu, Ira C.; Tuttle, Robert W., 1963- (Grand Rapids, Michigan : Eerdmans Publishing Company, 2014)
In this book Ira Lupu and Robert Tuttle break through the unproductive American debate over competing religious rights. They present an original theory that makes the secular character of the American government, rather than a set of individual rights, the centerpiece of religious liberty in the United States. Through a comprehensive treatment of relevant constitutional themes and through their attention to both historical concerns and contemporary controversies, including issues often in the news, Lupu and Tuttle define and defend the secular character of U.S. government.
Introduction : A secular government for a religious people -- Part I. Civil government and religious institutions -- Civil authority and the self-government of religious communities -- Government funding of religion -- Part II. Religion inside government -- Religious expression in public schools -- Religious expression in the public square -- Part III. Government and the people's religious liberty -- The core of religious liberty -- Government responsiveness to a religious people : forms and limits -- Conclusion. The military chaplaincy : a concluding case study -- Appendix : Authors' note on Town of Greece v. Galloway.
Includes bibliographical references and index.
Print version record.
Keywords: Church and state -- United States; Christianity and politics -- United States; Christianity and politics; Church and state; United States; Religion; Staat; Kirche; Säkularismus.; Religionsfreiheit; USA; POLITICAL SCIENCE / Political Process / Political Advocacy; Electronic books